Teenagers’ Attitudes Towards Franglais in France and Francophone Switzerland - Deboffe, Mathieu (Cahiers du Centre de Linguistique et des Sciences du Langage, 2016)
The insertion of English items into the French language has gradually become more and more common since the 1950s: from e-mail through to lunch bag, French is now pervaded by English words. Elaborating on this observation, this article examines and compares the attitudes to these words – belonging to the franglais paradigm – as reported by teenagers of France and francophone Switzerland. Based on empirical questionnaire- derived data, it shows, after a quick review of the sociolinguistic background of each area of investigation that the use and perception of franglais among teenagers is similar in the two countries, where franglais appears to be frequently used and favourably considered.